2018
DOI: 10.3892/ol.2018.9854
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the BDNF/TrkB pathway for the treatment of tumors (Review)

Abstract: Neurotrophins are a family of growth factors that regulate neural survival, development, function and plasticity in the central and the peripheral nervous system. There are four neurotrophins: nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3) and NT-4. Among them, BDNF is the most studied due to its high expression in the brain. Over the past two decades, BDNF and its receptor tropomyosin receptor kinase B (TrkB) have been reported to be upregulated in a wide range of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 108 publications
(149 reference statements)
1
73
0
Order By: Relevance
“…TrkB has been reported to regulate cellular proliferation in various cancer cells (reviewed in [12,27]). In accordance with this notion, TrkB knockdown in the SK-N-SH cell line in hypoxia caused inhibition of cellular proliferation in this study ( Figure 2I).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TrkB has been reported to regulate cellular proliferation in various cancer cells (reviewed in [12,27]). In accordance with this notion, TrkB knockdown in the SK-N-SH cell line in hypoxia caused inhibition of cellular proliferation in this study ( Figure 2I).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that TrkB activation initiates three downstream signaling cascades, namely PI3K/AKT/mTOR, Ras/extracellular signal-regulated kinase (ERK), and phospholipase C-γ/protein kinase C (PLCγ/PKC) [12,27]. The activating mutations of the K-ras gene constitutively turn on the downstream K-ras-transduced signaling pathways, Ras/ERK and PI3K/AKT.…”
Section: Discussionmentioning
confidence: 99%
“…It exerts its effects on brain function, including neuroprotection, vascular remodelling, neurogenesis, neuronal survival, and neuroplasticity, following injury to brain cells, particularly after ischemic insults (Chao, 2003;Ohira and Hayashi, 2009;Lu et al, 2013). Additionally, BDNF regulates neuronal survival, cell migration, and synaptic function (Thoenen, 1995;Murer et al, 2001;Baydyuk and Xu, 2014;Lu et al, 2014;Meng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…NTRK2 was shown to serve as an oncogene in multiple cancers (19)(20)(21)(22), and its increased expression was associated with poor outcome (23,24). Based on this, inhibition of NTRK2-encoded TRKB was shown to induce antitumor effects and cellular apoptosis (25,26). Similar to NTRK1, NTRK3 has been demonstrated to be an oncogene in breast cancer and gastric cancer (27,28), but it acts as a tumor suppressor gene in CRC, neuroblastomas, and head and neck squamous cell carcinoma (10,29,30).…”
Section: Introductionmentioning
confidence: 99%